2011
DOI: 10.1021/je200263g
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Titration Study of the Temperature and Ionic Strength Dependence of the Acidity Constants of Nicotinic Acid (Niacin)

Abstract: The influence of temperature (T) and ionic strength (I m ) on the stoichiometric (molality scale) acidity constants of nicotinic acid in aqueous solution was investigated by potentiometry (H þ -glass electrode). The background salt used was potassium chloride, and the temperature and ionic strength ranges covered were 283.15 K < T < 318.15 K and 0.05 mol 3 kg À1 < I m < 0.52 mol 3 kg À1 , respectively. Acidity constants at zero ionic strength were derived by means of a DebyeÀH€ uckel type formalism, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The FA or MA content was further determined by UV–vis spectrophotometry at 210 and 206 nm, respectively. The titrations were carried out with a Radiometer Analytical pHC3001-9 combined pH electrode and a previously described setup and procedure . Spectrophotometric measurements were performed on a Shimadzu UV-1800 apparatus equipped with a TCC-240A cell holder connected to a TCC temperature controller.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The FA or MA content was further determined by UV–vis spectrophotometry at 210 and 206 nm, respectively. The titrations were carried out with a Radiometer Analytical pHC3001-9 combined pH electrode and a previously described setup and procedure . Spectrophotometric measurements were performed on a Shimadzu UV-1800 apparatus equipped with a TCC-240A cell holder connected to a TCC temperature controller.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Several analytical studies followed, using TLC [10][11][12][13][14], spectrophotometric [15][16][17][18], and HPLC methods [19][20][21]. Capillary electrophoresis and HPLC methods were Separations 2021, 8, 46 2 of 11 developed to determine NIA in foods [22] via autoclaving at 121 • C in the presence of 0.8 M sulfuric acid for 2 h. Potentiometric and voltametric studies have also been reported in the literature [23,24]. Although the thermal stability of NIA was a controversial topic [25], many gas chromatographic methods were developed for the determination of NIA in food samples and in enzymes, relying on short analysis time, low molecular weight of NIA and high volatility [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The high nonlinear efficiency of an organic material is due to the long wavelength absorption edge since they have delocalised conjugated π electron to enhance the nonlinear hyper polarizability [7]. The organic NLO materials have excellent applications in optical data storage, optical information processing, electro optical modulation, telecommunication, etc., [8][9][10].…”
Section: Introductionmentioning
confidence: 99%